2012
DOI: 10.4103/2277-9175.100188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red grape juice on Alzheimer′s disease in rats

Abstract: Background:Alzheimer's disease is a neurodegenerative disease appearing as a result of free radicals and oxidative stress. Antioxidants agents boost memory and control Alzheimer's disease. Since red grape juice contains antioxidant agents, its effects on speed of learning and improvement of memory was studied in Alzheimer's rats.Materials and Methods:Alzheimer's model was induced by bilateral infusion of streptozocine into lateral ventricles of brain of male rats. Rats drank 10% red grape juice for 21 days. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a different study conducted by Siahmard et al (2012), male rats were given injections of streptozocin in both lateral ventricles of the brain to cause AD by causing a biochemical and oxidative imbalance, and then were given diluted grape extract to examine the association between Vitis vinifera juice consumption and AD. The passive avoidance test data showed that AD rat models had their memory and learning abilities reduced, while AD rat models that drank red grape juice had their memory and learning abilities improved.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study conducted by Siahmard et al (2012), male rats were given injections of streptozocin in both lateral ventricles of the brain to cause AD by causing a biochemical and oxidative imbalance, and then were given diluted grape extract to examine the association between Vitis vinifera juice consumption and AD. The passive avoidance test data showed that AD rat models had their memory and learning abilities reduced, while AD rat models that drank red grape juice had their memory and learning abilities improved.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 99%
“…The passive avoidance test data showed that AD rat models had their memory and learning abilities reduced, while AD rat models that drank red grape juice had their memory and learning abilities improved. Consequently, it is advised to employ Vitis vinifera in the future to prevent the progression of AD (Siahmard et al, 2012).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 99%
“…Evidence has been provided that extracts from grape skin and grape seed can inhibit Aβ aggregation, presenting an AD treatment potential [ 271 ]. In an AD rat model, red grape juice intake has been found to increase learning speed and improve memory [ 272 ]. Grape seed proanthocyanidins presented the capacity to ameliorate neuronal oxidative damage and cognitive impairment in an experimental AD model [ 273 ].…”
Section: Neuroprotective Natural Products For Admentioning
confidence: 99%